(untitled) (Voice of Teacher, 2023)
Banking is an important institution and in banking too, there are many more offences over its activities. Law is a formal tool to socially control such activities. The article is an analysis of such discourses. The factors that come into play while the Judiciary delivers verdict to some particular banking offence case are not solely technical; for social aspects also come into play. Laws are made with reference to some particular state of society; and need to be complemented with certain assumptions and extrapolations when used in a different state of society. This creates room for multiple explanations as shown in the different case studies listed in this paper.